High-risk clones of ESBL-producing Klebsiella pneumoniae colonizing ICU patients in Natal, northeastern Brazil - Fortaleza Neves Bomfim, Isabela Maria (2023)
Background and objectives: colonization by extended-spectrum β-lactamase (ESBL)-producing Klebsiella pneumoniae in Intensive Care Unit (ICU) patients is considered a risk factor for infections, and poses as a source of spreading these strains in hospital facilities. This study aimed to perform the genetic characterization of ESBL-producing K. pneumoniae isolates recovered from surveillance swabs in an ICU in northeastern Brazil. Methods: the isolates were recovered between 2018-2019 from the nasal, axillary, and rectal sites of 24 patients admitted to the ICU. Bacterial identification was performed by traditional biochemical tests. Antimicrobial susceptibility was assessed by disk diffusion, and ESBL phenotype was detected by double-disc synergy test. Polymerase chain reaction (PCR) for blaCTX-M, blaSHV, and blaTEM genes, PFGE, and MLST were carried out in representative isolates. Results: a total of 27 isolates were recovered from 18 patients (75%). The ESBL production was detected in 85% of isolates. Resistance to ciprofloxacin, sulfamethoxazole/trimethoprim and most of the β-lactams tested was recurrent, except for carbapenems. The blaSHV, blaTEM, and blaCTX-M genes were found in high frequency, and the CTX-M-(1, 2 and 9) groups were identified. Seven sequence types (ST11, ST14, ST17, ST395, ST709, ST855, and ST3827) were described, most of them considered high-risk. Conclusion: these findings emphasize the potential threat of well-established high-risk clones in an ICU, and highlight the importance of monitoring these clones to prevent infections.